Feeding practices among tribal mothers of malnutrition prevalent region of Amravati District in India - Mahure, Pankaj; Gurjar, Yashashree; Sawkar, Jitendra (Indian Journal of Child Health, 2017)
Introduction: Due to lack of intra- and post-natal care, the feeding practices can lead to a number of morbidities in the infancy period. Infant care in the community is influenced by cultural practices prevalent in the specific area apart from medical and economic reasons. Objectives: The objectives of this study were to understand prevalent feeding practices among tribal mothers having children <3 years of age and to explore reasons behind these practices. Methods: This community-based cross-sectional descriptive study was done in the northern tribal region of Amravati district. A total of 312 mothers were selected randomly for the study. Data were collected through face-to-face interviews of mothers who had a child of age <3 years using the structured interview. Results: Nearly 35% of mothers gave colostrum to the baby after 1 h of birth. While 39% of mothers were not found to be feed colostrum to the baby due to family tradition or advice of the elders, and 68% rejected colostrum feeding because they thought it was not clean. As high as 90% of the mothers initiated complementary feeding to the baby between 6 and 8 months of age, whereas 59% of children suffered from illness during 6 months immediately preceding the study. Conclusion: Inappropriate feeding practices need to be corrected to ameliorate the nutritional and health status of infants in a tribal region in India.